Konstruksi Makna Setara Melalui Perilaku Patriarkis Perempuan di Ruang Domestik dan Publik: Studi Kasus Kepada Anggota LSM Perempuan Di Yogyakarta - Miranti, Adita; Wibawa, Raja Satria (Jurnal InterAct, 2021)
Gender basically discusses the meaning of equality between women and men in various aspects of life. The existence of men and women are two entities that are often distinguished in terms of sex and the roles that must be performed gender so that the potential to cause disparity. The purpose of this study is to analyze how the construction of the meaning of "equal" in the study of gender equality is based on the perspective of men and women. This study uses a case study research method with in-depth interview techniques, observation, and literature review in the form of books, journals, and relevant articles. The results of this study indicate that the meaning of equality is generally closely related to women who are often treated unfairly and become inferior. The construction of the meaning of "equal" now turns out to be able to discredit men through the dogmatic state that develops in society. On the other hand the situation of gender equality is currently experiencing a shift in behavior, namely the emergence of superiority of women over men in the public and domestic spheres.